Effects of Group Psychotherapy on Young Adults' Romantic and Career Functioning. (March 2017) - Shulman, Shmuel; Rozen-Zvi, Ruth; Almog, Zhava; Fennig, Shmuel; Shavit-Pesach, Tamar
A growing number of young adults have difficulties meeting developmental challenges and experience psychological distress as a consequence of which they seek help to address these difficulties. A time-limited group psychotherapy focusing on addressing age-related tasks was developed to meet the needs of young people. Thirty-one young people seeking psychological help participated in 16 to 18 sessions of group psychotherapy. Psychological distress and goal pursuit capabilities were assessed at the beginning and the end of therapy. Compared with young people on a waiting list, participants undergoing group psychotherapy showed a significant decrease in psychological distress and increase in adaptive goal pursuit and independent functioning. Our findings indicate the importance of integrating a developmental perspective in group intervention to enhance young adults' competence in handling age-related tasks, as well as to improve their well-being.